Epigenetic Aspects of Engineered Nanomaterials: Is the Collateral Damage Inevitable? - Gedda, Mallikarjuna Rao; Babele, Piyoosh Kumar; Zahra, Kulsoom; Madhukar, Prasoon (Frontiers in Bioengineering and Biotechnology, 2019)
The extensive application of engineered nanomaterial (ENM) in various fields increases the possibilities of human exposure, thus imposing a huge risk of nanotoxicity. Hence, there is an urgent need for a detailed risk assessment of these ENMs in response to their toxicological profiling, predominantly in biomedical and biosensor settings. Numerous “toxico-omics” studies have been conducted on ENMs, however, a specific “risk assessment paradigm” dealing with the epigenetic modulations in humans owing to the exposure of these modern-day toxicants has not been defined yet. This review aims to address the critical aspects that are currently preventing the formation of a suitable risk assessment approach for/against ENM exposure and pointing out those researches, which may help to develop and implement effective guidance for nano-risk assessment. Literature relating to physicochemical characterization and toxicological behavior of ENMs were analyzed, and exposure assessment strategies were explored in order to extrapolate opportunities, challenges, and criticisms in the establishment of a baseline for the risk assessment paradigm of ENMs exposure. Various challenges, such as uncertainty in the relation of the physicochemical properties and ENM toxicity, the complexity of the dose-response relationships resulting in difficulty in its extrapolation and measurement of ENM exposure levels emerged as issues in the establishment of a traditional risk assessment. Such an appropriate risk assessment approach will provide adequate estimates of ENM exposure risks and will serve as a guideline for appropriate risk communication and management strategies aiming for the protection and the safety of humans.